Analysis of the Relationship between Green Marketing Initiatives and Consumer Purchase Decisions in Developing Economies - Aen Fariah (Politeknik Siber Cerdika Internasional, 2025)
Climate change and environmental damage have increased consumer awareness of the importance of sustainability, prompting many companies to adopt green marketing initiatives. In countries with developing economies, where environmental awareness is still in the developing stage, understanding the impact of these initiatives on consumer purchasing decisions is crucial. This study aims to analyze the relationship between green marketing initiatives implemented by companies and consumer purchasing decisions in developing economies. The method used was a quantitative survey involving 300 respondents in various market segments in Indonesia, where data was collected through questionnaires that measured consumer attitudes towards green products and purchase decisions. The results of the analysis show that green marketing initiatives significantly influence consumer purchasing decisions, with factors such as environmental awareness and perception of the value of green products playing an important role in moderating this relationship. This research provides insights for companies on the importance of communicating sustainability values and the benefits of green products to increase consumer loyalty and purchasing decisions. These findings also contribute to the literature on green marketing in the context of developing economies.